2020
DOI: 10.1038/s41535-020-0216-6
|View full text |Cite
|
Sign up to set email alerts
|

The range of non-Kitaev terms and fractional particles in α-RuCl3

Abstract: Significant efforts have focused on the magnetic excitations of relativistic Mott insulators, predicted to realize the Kitaev quantum spin liquid (QSL). This exactly solvable model involves a highly entangled state resulting from bond-dependent Ising interactions that pro-1 arXiv:2003.09274v1 [cond-mat.str-el] 18 Mar 2020 duce excitations which are non-local in terms of spin flips. A key challenge in real materials is identifying the relative size of the non-Kitaev terms and their role in the emergence or supp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 72 publications
(151 reference statements)
3
39
0
Order By: Relevance
“…However, many recent studies have found high temperature signatures of these exotic states or proximity thereto. For example, recent spectroscopic and thermodynamic studies of α-RuCl 3 [11][12][13][14][15][16][17][18] , have reported evidence for the onset of nearest-neighbor Kitaev correlations, consistent with a proposal by Motome and co-authors of a thermal crossover from a paramagnet to a spin-"fractionalized" state [19][20][21] . Similar studies have extended these conclusions to α, β, γ−Li 2 IrO 3 and α−Na 2 IrO 3 systems 22-24 . In the case of the β− and γ-Li 2 IrO 3 systems this temperature range is also associated with strong deviations from Curie-Weiss susceptibility, and a dramatic re-ordering of the principal axes of magnetization.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, many recent studies have found high temperature signatures of these exotic states or proximity thereto. For example, recent spectroscopic and thermodynamic studies of α-RuCl 3 [11][12][13][14][15][16][17][18] , have reported evidence for the onset of nearest-neighbor Kitaev correlations, consistent with a proposal by Motome and co-authors of a thermal crossover from a paramagnet to a spin-"fractionalized" state [19][20][21] . Similar studies have extended these conclusions to α, β, γ−Li 2 IrO 3 and α−Na 2 IrO 3 systems 22-24 . In the case of the β− and γ-Li 2 IrO 3 systems this temperature range is also associated with strong deviations from Curie-Weiss susceptibility, and a dramatic re-ordering of the principal axes of magnetization.…”
Section: Introductionsupporting
confidence: 73%
“…On the other hand, evidence for such fractionalization in this temperature range has been reported in α-RuCl 3 and α-Li 2 IrO 3 . [11][12][13][14][15][16]18,62,63 The fact that this appears as a crossover in the α-type structures and a phase transition in β, γ-type structures may simply reflect the different dimensionality of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most promising theoretical models of QSLs is the Kitaev model based on interacting spin-1/2 ions on a two-dimensional honeycomb lattice with bond-dependent Ising axes [4]. The prime candidates for the Kitaev model are α-Li 2 IrO 3 , Na 2 IrO 3 , and α-RuCl 3 , but all three compounds order magnetically at low temperatures [5][6][7][8][9][10]. Recently, a new class of intercalated Kitaev magnets was synthesized via a topochemical exchange of the interlayer Li/Na atoms in α- [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a series of Raman studies (both experimental and theoretical) on a range of spin-orbit coupled (SOC) Mott insulators, with a view to elucidate the nature of their magnetic excitations (and lattice dynamics) and their proximity to the so-called Kitaev quantum spin liquid ground states . Most saliently, the reported Raman scattering data in the Kitaev candidate materials α-RuCl 3 [13,14,[17][18][19] and the three-dimensional (3D) iridates β-Li 2 IrO 3 and γ -Li 2 IrO 3 [16], revealed signatures of both multiparticle continua, characteristics of the proximate spin liquid phase, and sharp peaks, characteristic of magnon excitations of the low-temperature ordered phases. These results call for a close reexamination of the Raman scattering theory applied to strong spin-orbit coupled Mott insulators.…”
Section: Introductionmentioning
confidence: 99%